Analysis of alcohol policy in Nigeria: multi-sectoral action and the integration of the WHO “best-buy” interventions (2019)
Background: Harmful alcohol use is a modifiable risk factor contributing to the increasing burden of non-communicable diseases and deaths and the implementation of policies focused on primary prevention is pivotal to address this challenge. Policies with actions targeting the harmful use of alcohol have been developed in Nigeria. This study is an in-depth analysis of alcohol-related policies in Nigeria and the utilization of WHO Best Buy interventions (BBIs) and multi-sectoral action (MSA) in the formulation of these policies. Methods: A descriptive case study design and the Walt and Gilson framework of policy analysis was utilized for the research. Components of the study included a scoping review consisting of electronic search of Google and three online databases (Google Scholar, Science Direct and PubMed) to identify articles and policy documents with no language and date restrictions. Government institution provided documents which were not online. Thirteen policy documents, reports or articles relevant to the policy formulation process were identified. Other components of the study included interviews with 44 key informants (Bureaucrats and Policy Makers) using a pretested guide. The qualitative data were coded and analyzed using thematic analysis. Results: Findings revealed that policy actions to address harmful alcohol use are proposed in the 2007 Federal Road Safety Act, the Non-communicable Diseases Prevention and Control Policy and the Strategic Plan of Action. Only one of the best buy interventions, (restricted access to alcohol) is proposed in these policies. Multi-sectoral action for the formulation of alcohol-related policy was low and several relevant sectors with critical roles in policy implementation were not involved in the formulation process. Overall, alcohol currently has no holistic, health-sector led policy document to regulate the marketing, promotion of alcohol and accessibility. A major barrier is the low government budgetary allocation to support the process. Conclusions: Nigeria has few alcohol-related policies with weak multi-sectoral action. Funding constraint remains a major threat to the implementation and enforcement of proposed policy actions.